Mechanism of aroma compounds changes from sea cucumber peptide powders (SCPPs) under different storage conditions. (February 2020) - Li, Xinran; Wang, Ke; Yang, Ruiwen; Dong, Yifei; Lin, Songyi
Graphical abstract: Highlights: Investigate the changes of aroma compounds in SCPPs under the storage conditions. Volatile compounds in SCPPs were identified by a GC-IMS Flavor analyzer. Investigate the effects of moisture absorption on the SCPPs' aroma during storage. Explore the effects of the microorganisms on the SCPPs' aroma during storage. Abstract: A rapid and sensitive measurement technique was used to investigate the mechanism of aroma compounds changes in SCPPs under the storage conditions with hygroscopicity and no-microorganism (HNM), nonhygroscopicity and no-microorganism (NHNM) and hygroscopicity and microorganism (HM) by HS-GC-IMS. The types and signal of aroma compounds increased obviously at the 5th day under the storage condition (HNM and HM). The signal of majority of aroma compounds decreased gradually since the 5th day. However, during the storage of SCPPs for 15 days, the total signals of aldehydes, ketones and alcohols gradually increased and reached a maximum. Thereinto, the saturated aldehydes such as hexanal had been produced as an off-flavor. These off-flavor compounds principally including aldehydes and ketones could be generated through Maillard reaction, while alcohols could be generated by microbial fermentation. The study discovered moisture adsorption and microorganism during storage could affect aroma compounds of SCPPs and the effect of moisture absorption was greater than microorganisms.